PELATIHAN PEMBUATAN BLOG BRANDING USAHA TOKO JIHAN PADANG - Nasir, Januardi; Setiawan, Yasha Langitta; Anwar, Hendra (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2023)
Rapid development in the business world in the city of Padang, coupled with an increasing demand from the predominantly working population, requires business actors to adopt creative ideas to thrive in the intensifying competition. In this context, branding emerges as one of the strategic solutions. This study aims to leverage a blog as a tool for branding and promotion for Toko Jihan in the city of Padang. The method involves creating and managing a free blog, along with adjusting the content to meet business needs. Despite utilizing social media platforms such as Facebook and Instagram for marketing, the owner still feels less confident without a means of information delivery like a blog or website. The outcomes of this community service activity encompass three solution steps: blog selection and creation, blog content creation, and blog maintenance. Blog selection focuses on the sustainability of the business by choosing a free platform that can be modified. Content creation involves product information, while blog maintenance discusses actions to ensure continuity and optimize performance. In conclusion, using a blog as a branding tool can boost the owner's confidence and optimize the visibility of Toko Jihan. The applied solution steps are expected to positively contribute to business development amid intense competition.